MAKNA DAN NILAI UPACARA ADAT TAHUN BARU PADI (NGARANTIKA) MASYARAKAT DAYAK SALAKO DI KECAMATAN SAJINGAN BESAR SAMBAS - Alberta Febi Astri; Agus Sastrawan Noor; F. Y. Khosmas (Universitas Tanjungpura, 2020)
AbstractThis study aims to describe the meaning and value in the traditional rice ceremony (Ngarantika) in Santaban Village, Sajingan Besar District, Sambas Regency. The approach in this study uses a qualitative approach with a descriptive method, which is a research model that seeks to make a careful and in-depth picture of the meaning and value in the implementation of the New Year's Rice ceremony (Ngarantika). Data sources in this study are the Village Secretary, Traditional Figure and Religious Figure. The results showed that the implementation of the traditional ceremony for the new year of rice had fourteen stages. six meanings of offerings or props prepared in the traditional ceremony of the New Year's Rice (Ngarantika), namely: 1. chicken (Manok), 2. bontokng, 3. lemang (Poe), 4. cucur (Tumpi), 5. antek , and 6. tepung tawar(tapukng tawar) . Offerings play an important role in the traditional ceremony of the new year of rice because as a means of introducing prayers to God. The offerings in the form of staple food symbolize the welfare of the Dayak Salako who are very well-off in all respects. There are five cultural values contained in the New Year's Rice Ceremony (Ngarantika) which need to be emulated by the Salako Dayak community, namely: 1. Religious Value. 2. Value of Respect for Ancestors and Nature. 3. Social Value. 4. Mutual Assistance Value, and 5.Sharing Value. Keywords:Meaning of Symbols, Cultural Values, New Year’s Rice Ceremony (Ngarantika)